Current scenario and challenges of clinical pharmacists to implement pharmaceutical care in DRG/DIP payment hospitals in China: a qualitative interview study - Gao, Suyu; Wang, Xuanxuan; Lu, Yun; Liu, Yunkun; Jiang, Qiaoli; Feng, Jiajia; Kong, Weihua; Lin, Likai; Cheng, Hong (Frontiers in Public Health, 2024)
The Diagnosis-Related Group (DRG) or Diagnosis-Intervention Packet (DIP)payment system, now introduced in China, intends to streamline healthcare billing practices. However, its implications for clinical pharmacists, pivotal stakeholders in the healthcare system, remains inadequately explored.This study sought to assess the perceptions, challenges, and roles of clinical pharmacists in China following the introduction of the DRG or DIP payment system. Methods: Qualitative interviews were conducted among a sample of clinical pharmacists. Ten semistructured interviews were conducted, either online or face to face. Thematic analysis was employed to identify key insights and concerns related to their professional landscape under the DRG or DIP system.Results: Clinical pharmacists exhibited variable awareness levels about the DRG or DIP system.Their roles have undergone shifts, creating a balance between traditional responsibilities and new obligations dictated by the DRG or DIP system. Professional development, particularly concerning health economics and DRG-based or DIP-based patient care, was highlighted as a key need. There were calls for policy support at both healthcare and national levels and a revised, holistic performance assessment system. The demand for more resources, be it in training platforms or personnel, was a recurrent theme.The DRG or DIP system's introduction in China poses both opportunities and challenges for clinical pharmacists. Addressing awareness gaps, offering robust policy support, ensuring adequate resource allocation, and recognizing the evolving role of pharmacists are crucial for harmoniously integrating the DRG or DIP system into the Chinese healthcare paradigm.